2018
DOI: 10.1007/s12519-018-0145-7
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality of coagulase-negative staphylococcal sepsis in very-low-birth-weight infants

Abstract: CoNS sepsis was not associated with mortality or morbidities other than length of stay. These findings support vancomycin-reduction strategies in the NICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…[11,12,45,47,50] As far as the type of bacteria resulted in the sepsis, 4 studies identified the specific bacteria. Three of them [13,23,30] investigated the relationship of coagulase-negative Staphylococcus (CoNS) sepsis and ROP. However, there was no study to identify the different impact factors on ROP between bacterial and fungal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12,45,47,50] As far as the type of bacteria resulted in the sepsis, 4 studies identified the specific bacteria. Three of them [13,23,30] investigated the relationship of coagulase-negative Staphylococcus (CoNS) sepsis and ROP. However, there was no study to identify the different impact factors on ROP between bacterial and fungal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of CoNS impact on the clinical field was emphasized by the extensive medical progress, where the use of implantable medical devices and the increasing number of vulnerable patients have allowed CoNS to cause significant infections in humans [10]. More importantly, these factors have elevated the number of morbid, chronically ill and immunocompromised patients, as well as the mortality rates related to CoNS [11,12]. Moreover, as CoNS are known to colonize both farm and domestic animals, they may as well establish infections upon opportunity, although to a lesser extent.…”
Section: Introductionmentioning
confidence: 99%
“…In this retrospective hospital-based cohort study, we found the overall incidence of LOS in VLBW infants over 7 years was 24.08% and culture-proven LOS was 19.58%, which was similar to the reports from South America, 7 Korea, 1 Brazil, 13 lower than that of Saudi Arabia 10 or Guangzhou of China 9 but higher than that of Hongkong 5 or Beijing of China, 8 Texas of USA. 14 This may be due to disparities in measures of infection control, years of investigation, the definition of LOS, and study criteria for inclusion and exclusion. In general, the incidence of LOS in VLBW preterm infants was higher than that in overall neonates.…”
Section: Discussionmentioning
confidence: 99%